2014
DOI: 10.1128/mbio.01193-14
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Nitrous Oxide Reductase ( nosZ ) Genes in Soil Metagenomes: Method Development and Implications for the Nitrogen Cycle

Abstract: Here, we analyzed the abundance and diversity of both nosZ types in whole-genome shotgun metagenomes from sandy and silty loam agricultural soils that typify the U.S. Midwest corn belt. First, different search algorithms and parameters for detecting nosZ metagenomic reads were evaluated based on in silico-generated (mock) metagenomes. Using the derived cutoffs, 71 distinct alleles (95% amino acid identity level) encoding typical or atypical NosZ proteins were detected in both soil types. Remarkably, more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
117
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 39 publications
(62 reference statements)
14
117
0
Order By: Relevance
“…Quantitative PCR data and metagenomic analyses revealed that nosZ genes affiliated with the Anaeromyxobacter genus are abundant in agricultural soils of the U.S. Midwest corn belt (15,19). The results of Anaeromyxobacter genome analyses suggest that members of this genus do not possess NO-forming nitrite reductase genes (nirK or nirS) but share a clade II nosZ gene (15).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Quantitative PCR data and metagenomic analyses revealed that nosZ genes affiliated with the Anaeromyxobacter genus are abundant in agricultural soils of the U.S. Midwest corn belt (15,19). The results of Anaeromyxobacter genome analyses suggest that members of this genus do not possess NO-forming nitrite reductase genes (nirK or nirS) but share a clade II nosZ gene (15).…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, P. stutzeri had a growth yield 1.8-fold lower than the value measured for Anaeromyxobacter dehalogenans strain 2CP-C. Fast-growing r-strategists are rarely abundant in nutrient-limited soil environments, and the slow-growing K strategists (e.g., Anaeromyxobacter, Opitutus, and Gemmatimonas populations) are generally more robust under such conditions (19,46,47). Competition experiments performed under controlled N 2 O flux conditions will provide further insights and directly reveal the relevance of clade I versus clade II organisms for modulating soil N 2 O emissions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Metagenomic analyses of environmental DNA have revealed that clade II nosZ genes are, in fact, abundant in diverse environments, ranging from tropical forest and hot desert to Arctic tundra and polar desert (18,22). Among the most abundant phylogenetic groups of nosZ in the environment are clade II nosZ genes affiliated with the Gemmatimonadetes phylum (16,18).…”
mentioning
confidence: 99%